Possibilidades e limites da justiça restaurativa para resolução de conflitos domésticos - Hilda Maria Porto de Paula Teixeira da Costa (2023)
This work aims to demonstrate whether Restorative Justice is suitable for resolving family conflicts with domestic violence. From the concept of Restorative Justice, its principles, values and models, as well as from the understanding of what violence is, and the existing species in domestic violence. Violence, analyzed from its sociological and psychological aspects, allows us to verify the consequences resulting from it: trauma and shame. All these deeply considered themes are appreciated under the relevant normative frameworks, in order to verify the adequacy of Restorative Justice also under the practical plan, as the empirical research analyzes the Brazilian experiences mainly, in the State of Minas Gerais. After all, the limits and possibilities of Restorative Justice action in cases related to Domestic Violence are descriptively presented, with the formulation of proposals for its improvement.